The Implementation of Good Governance in the Era of Caliphate Omar Ibn Abd al-Aziz (61H-101 H/717-720 M) - Handoko, Luqman Hakim; Kayadibi, Saim (Faculty of Islamic Economics and Business - State Islamic University, Sunan Kalijaga Yogyakarta, 2013)
The discussions of good governance are being widely debatable all over the world. The world has arrived at an agreement that good governance has major influence for human resource development in the society. The debate is currently, going on all sectors of activities such the social, economic, and political imperatives, cultural sources and traditions. These have contribution to supervise and govern societies, how to manage business enterprises. The purpose of this paper is to investigate and to understand the theory of good governance from both a modern and Islamic perspective. Firstly, this paper is aimed to find out what is the good governance in modern term. Secondly, this paper will try to explore and explain the siyasah shar‟iyyah means concerning to good governance on modern societies. Thirdly, explaining and exploring the concept of good governance in the reign of caliph Omar ibn Abd al-Aziz. It already known that within short time he was able to bring the khilafah to glorious administration. This paper find that it is believed that the concept of good governance already practised by Caliph Omar ibn Aziz throughout his reign. In addition, there are many successes have been achieved by Omar either in the field of economy, politics and national defense and religious fields where the field may be difficult to achieve today's leaders. Keywords: Good Governance; Siyasah Shar‘iyyah; Maqasid Shari‘ah; Omar Ibn Abd al Aziz (61H-101 H) ; Public Policy